Molecular characterization of some scented rice varieties - DILEEP KUMAR MASUTHI,; V. K. DESHPANDE,; B. S. VYAKARNAHAL,; S. KHAJA RUBINA, (Seed Research, 2026)
Locally popular forty one scented land races were collected from northern Karnataka. These genotypes were analyzed by SSR markers. Of the 10 SSR markers used in the study only 9 markers were able to distinguish the aromatic rice genotypes. A set of 4 informative SSR markers (CHR-4-8, CHR-8-34, CHR-8-29 and CHR-8-6) could analyze closely related genotypes. These primers amplified a total of 24 profiles across 32 scented rice genotypes. Cluster analysis based on Unweighted Pair Group Method Average Analysis (UPGMA) led to recognition of 4 clusters. Cluster I was the largest with 26 genotypes followed by cluster III. Genetic diversity among some of these cultivars indicated that the cultivars can effectively contribute to the gene pool of aromatic rice cultivars.